Positive resources: feeling of hope and life satisfaction in a group of patients treated in childhood because of differentiated thyroid gland cancer - Syska-Bielak, Anna; Jarząb, Magdalena; Kropińska, Aleksandra; Heyda, Alicja; Handkiewicz-Junak, Daria; Hese, Robert; Jarząb, Barbara (Contemporary Oncology/Współczesna Onkologia, 2010)
Background : Differentiated thyroid cancers (DTC) are among the more frequent epithelial cancers in children. In this population they are characterized by more advanced stages and a stormier clinical course. By applying appropriate methods of integrated anti-cancer treatment, some excellent results can be achieved. The burden of the stigma of cancer disease and diagnostic-therapeutic procedures on patients’ further psychological functioning in adult life have not been analysed so far. The purpose of the research was to analyse satisfaction from life and the level of hope in patients treated in childhood for differentiated thyroid cancer. Material and methods : The study group comprised 71 persons (47 females and 24 males aged 18-56), diagnosed and treated at Zakład Medycyny Nuklearnej i Endokrynologii Onkologicznej Centrum Onkologii – Instytutu im. Marii Skłodowskiej-Curie, Oddział w Gliwicach. All the patients had completed the first stage of treatment (medical examination at least two years after being diagnosed). Life satisfaction was graded with the Life Satisfaction Scale (E. Diener, R.A Emmons, R.J. Larson and S. Griffin, Polish adaptation Z. Juczyński) and level of hope with Cantril’s Ladder. Results and conclusions : Life satisfaction and hope, as positive resources, are vital factors of personality and give zest for life as well as helping to set subsequent life goals. Most patients evaluate their life satisfaction and level of hope rather highly. The level of life satisfaction in the study group was 21.8 points on average, which corresponds to a value of 8 on the sten scale. Only 7% of patients in the group showed low results in the SWLS test with marks below 4 points on the sten scale. The level of hope in the study group was also evaluated. It was found that 43.6% of patients showed an optimistic attitude towards their health condition. A similar number of patients (43.6%) find their future situation similar to their present one (test results at the value of 0). Only in 12.8% was an unsatisfactory attitude towards their future reported. The problems of patients with negative attitudes towards their lives and future prospects will be presented in the context of family support.